PENERAPAN MODEL PEMBELAJARAN PACE (PROJECT, ACTIVITY, COOPERATIVE LEARNING, EXERCISE) UNTUK MENINGKATKAN KEMAMPUAN PEMBUKTIAN MATEMATIS PESERTA DIDIK SMA - derry aryadi; deti ahmatika (UJMES (Uninus Journal of Mathematics Education and Science), 2018)
The background of this research is the low mathematical proofing ability of students. One alternative learning that can be applied to improve students' mathematical proofing ability is the PACE learning. The purpose of this study is to find out: whether the students' mathematical evidentiary ability using the PACE learning is better than students who use PBL (Problem Based Learning) models, and how students respond to mathematics learning using the PACE learning. The research method is quasi-experimental, with a pretest-posttest control group design research design. The study was conducted in one of the state high schools in the city of Bandung. The study population was all students of class XI, the sample students of class XI MIPA-1 as the experimental class were given the PACE treatment and class XI MIPA-2 as the control class was given the PBL treatment. The research instrument was a mathematical proofing ability test, a student questionnaire, and an educator observation sheet. The results of the research are quantitative and qualitative data. Analysis of quantitative research results using t test, while qualitative results use a Likert scale. Based on the analysis of the results of the mathematical proofing ability test, it can be concluded that: the mathematical proofing ability of students by using the PACE learning model is better than the students who use PBL learning models, and the students' responses to mathematics learning using the PACE learning are positive.